Disclosure of competing interests. (12th October 2009) - Drazen, Jeffrey M; Weyden, Martin B Van Der; Sahni, Paush; Rosenberg, Jacob; Marusic, Ana; Laine, Christine; Kotzin, Sheldon; Horton, Richard; Hébert, Paul C; Haug, Charlotte; Godlee, Fiona; Frizelle, Frank A; et al.
Abstract : A new standardised format that all journals could use